Application of statistical techniques to identify the hydrogeochemical processes in coastal aquifers of Pondicherry region- Tamil Nadu - Thilagavathi, R.; Chidambaram, S.; Thivya, C.; Pethaperumal, S.; Tirumalesh, K.; Prasanna, Mohan Viswanathan (2014)
© 2014, Capital Publishing Company.Groundwater pollution can be illustrated as degrading of water quality for any usage. The Eleven hydrochemical parameters of groundwater samples from different formation were used in this study to understand groundwater chemistry in this complex multilayer aquifer system. The statistical analysis of the results shows that dominant process of weathering of feldspar, pyroxene and ion exchange. The water flows along the formation dissolving these ions along its flow path through the process of leaching of the secondary salts inherited in the formation obtained by the mixing of several geochemical processes. The anthropogenic impacts in the groundwater are noted in the younger formation than that of Cretaceous and Lower Cuddalore.